Soundwalk path affecting soundscape assessment in urban parks - Sun, Chutian; Meng, Qi; Yang, Da; Wu, Yue (Frontiers in Psychology, 2023)
Previous soundscape studies have substantially investigated the effect of sound perception and acoustic comfort in urban spaces. However, the effects of soundwalk paths on soundscape have not been sufficiently explored. Therefore, in this study, a typical urban park was selected as a case study. The differences, characteristics, and effects of soundwalk paths on the soundscapes were explored, based on a soundwalk survey and laboratory study. The results are as follows: first, different soundwalk paths in the urban park have significant effects on the perceived extent of individual sound and soundscape assessment. Second, the soundscape assessment is consistent with the peak-end rule. The location where the peak assessment of soundscape appears, at the end of the soundwalk paths, is critical to the overall soundscape assessment. Furthermore, the overall perceived extent of individual sound is strongly affected by the perceived extent of dominant sounds near the end, and at the end of the soundwalk paths. Third, we compared the sound loudness contrast path (noise-quiet/quiet-noise) and sound source contrast path (natural-artificial sound/artificial-natural sound). In the noise-quiet path, the assessment of acoustic comfort is higher than that in the quiet-noise path, and the assessment of subjective loudness is lower than that in the quiet-noise path (p < 0.01). The subjective loudness of the artificial-natural sound path is lower than that in the natural-artificial sound path (p < 0.05). Thus, the design of the soundwalk path is expected to enhance visitors’ soundscape assessment of urban parks.